The effectiveness & efficiency of e-invoice and company tax compliance in Bogor City - Rifqi Alpharizq Pranaja; Ratih Hendayani (Annals of Human Resource Management Research, 2025)
Purpose: This study examines whether the effectiveness and efficiency of Indonesia’s e-Invoice (e-Faktur) system and trust in government influence corporate tax compliance among firms in Bogor City. Research Methodology: A quantitative design was employed using a structured questionnaire administered to 200 corporate taxpayers that have used e-Invoicing. Data were analyzed through multiple linear regression (SPSS). Measurement quality was supported by validity, reliability (Cronbach’s Alpha), and classical assumption tests. Results: The findings indicate that e-Invoice effectiveness positively and significantly affects corporate tax compliance (β=0.657; p<0.05). e-Invoice efficiency also shows a positive and significant effect (β=0.317; p<0.05). In contrast, trust in government is significant but negatively related to compliance (β=-0.215; p<0.05), suggesting that compliance in a digitally monitored environment may be driven more by system enforcement and procedural certainty than by institutional trust. Collectively, the three predictors explain 55.4% of the variance in corporate tax compliance (R²=0.554). Conclusions: Improving the usability, reliability, and administrative speed of e-Invoicing can strengthen corporate tax compliance, while efforts to enhance service quality, transparency, and integrity are needed to address trust-related barriers. Limitations: The study is limited to Bogor City and does not incorporate broader external determinants (e.g., service quality, digital literacy, economic constraints). Contribution: This research extends e-tax compliance literature by simultaneously testing effectiveness, efficiency, and trust within the context of Indonesia’s tax digitalization and offering policy directions to optimize e-Invoice implementation.